(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this in vitro study was to evaluate the effect of using two different demineralizing agents on the micro-leakage of different retro-grade filling, the sealing ability of the MTA, & to compare the sealing ability of the three different retro-grade fillings. Seventy roots were selected, & the canals then instrumented utilizing crown down technique using pro-taper rotary files. All roots were obturated with non standardized gutta-percha master cones using the lateral condensation technique, apical root resections were made & root-end cavities were prepared. The prepared roots were randomly divided into seven experimental groups with 10 specimens in each; three groups demineralized by 17% EDTA, each group of them was filled with different retrograde filling materials either MTA , Resin-modified glass ionomer cement, or amalgam. The other three groups were demineralized by 35% phosphoric acid & each group of them was filled with the same different retrograde filling materials. The seventh group which is the control was filled with MTA without demineralization agent. The specimens were then placed in 2% methylene blue solution at (37°C, & pH 7) for 72 hours. To evaluate the depth of dye penetration, each root was sectioned longitudinally in a crown-apex direction. Linear dye penetration was measured using a stereomicroscope. Statistical analysis of the results revealed that the MTA had less leakage than the amalgam & the glass ionomer cement, & the difference was highly significant (p>0.01) for EDTA. In addition, the using of phosphoric acid had higher leakage than EDTA for MTA & GIC groups , however, the difference was non significant (p>0.05). MTA retro-filling material had better sealing ability than other materials used and the demineralizing agents may have effect on the quality of the micro-leak